Design and fabrication of frequency selective surface-based heating elements for radome applications using particle alignment technology - Daeyeong Yoon; Chul-Oh Park; Jae-Ho Kim; Yong Bae Park (Scientific Reports)
Abstract This paper presents a novel frequency selective surface (FSS) with embedded heating elements for radome applications, addressing the critical challenge of maintaining electromagnetic performance while providing effective de-icing capabilities. The proposed structure uniquely separates heating elements from radio wave transmission components, enabling independent control of thermal and electromagnetic characteristics. A bottom-up fabrication approach utilizing particle alignment technology was developed, achieving precise control of heating wire dimensions with minimum line widths of 1 µm and surface roughness below Rz 0.3 µm. The fabricated FSS demonstrated excellent transmission characteristics at 32 GHz with −0.298 dB (93.4%) for TE polarization and −0.283 dB (93.7%) for TM polarization, maintaining broad −1 dB transmission bandwidths. Thermal performance tests showed temperature increases exceeding 50 °C within 3 minutes under 12 VDC bias, while mechanical reliability tests confirmed durability through 5000 bending cycles at various curvature radii. The structure’s equivalent circuit model was developed and validated, explaining the polarization-dependent characteristics. This approach effectively resolves the traditional trade-off between heating and electromagnetic performance, offering a promising solution for high-performance radome applications requiring both thermal management and radio wave transmission capabilities.